Strategi Promosi Kesehatan melalui Komunikasi Digital : Studi @Halodoc di Instagram - Azzahra, Dwi Vira; Aidha, Zuhrina; Fahzirah, Ranti; Silangit, Nurhidayah; Apriansyah, Bagus Halfin; Difhanny, Chairunnisyah Nurma; Aliyyah, Annisa Fijjannah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
PT Media Dokter Investama has created an official Instagram account named @halodoc to ensure that messages can be conveyed quickly and comprehensively across Indonesia. Of course, PT Media Dokter Investama has the right communication strategy in digital media so that messages can be conveyed effectively and responded to by the public, or at the very least, read by the general public on Instagram. The purpose of this study is to analyze health promotion through digital communication on the @halodoc account on Instagram. Here, PT Media Dokter Investama uses Instagram as new media to convey information about health, tips, and health webinars. This is considered because the number of Instagram users in Indonesia is increasing every year, making Instagram an effective platform for conveying such information. Additionally, the dominant user segment of Instagram is millennials and adults. This is certainly related to the communication strategy conveyed by the @halodoc Instagram account because the information is quite scientific and only understood by young adults or adults.